Building the maritime paradigm of Sabah, Malaysia using the ecosystem-based management (EBM) model a premilitary study - Ismail bin Ali; Hinmin Bin Chiam Tah Kong; Mosli Tarsat (RSIS International, 2025)
This study aims to analyze the effectiveness of the Ecosystem-Based Management (EBM) model in developing the maritime paradigm in Sabah, in line with the national blue economy objectives that emphasize the sustainability of marine resources. Sabah, rich in marine natural resources, offers great potential in sectors such as fisheries, marine tourism, marine biotechnology, and marine energy. The main research question is how applicable the EBM model is in Sabah for strengthening marine resource management, improving synergy among various stakeholders, and driving the sustainable development of the maritime sector. The objectives of the study are to explore the potential of EBM in the context of Sabah's maritime sector, identify the challenges faced, and propose strategic steps to overcome these challenges. The study adopts a qualitative approach based on literature analysis and case studies from countries that have successfully applied the EBM model in managing their marine resources. The findings indicate that while the EBM model has significant potential in enhancing the sustainability of marine ecosystems, several challenges such as institutional capacity limitations, conflicts between stakeholders, and a lack of coordination between the public and private sectors need to be addressed for its effectiveness. This study suggests strengthening more holistic policies and regulations, enhancing cooperation between the government, private sector, local communities, and NGOs, as well as investing in technology and research to support effective EBM implementation. Overall, the study provides guidance for developing a more sustainable maritime paradigm in Sabah through the broader application of the EBM model. The way forward recommends a more inclusive approach that focuses on ecosystem conservation, while still encouraging high quality and competitive economic development.